Morphological and Phenological Responses of Sunflower to Nitrogen Fertilization and Plant Growth Promoting Rhizobacteria under Rainfed Conditions in Pakistan: Morpho-phenological responses of sunflower to plant growth promoting rhizobacteria and nitrogen - Qadeer, Abdul; Tahir, Majid Mahmood; Abbasi, Muhammad Kaleem; Ali, Ahsan; Rasheed, Adnan (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
Present study was conducted to evaluate the morphological and phenological responses of two sunflower (Helianthus annuus L.) cultivars (SFH-70 and RA-533) to nitrogen (N) fertilization and inoculation with plant growth promoting rhizobacterias (KS41 and KS42) during 2015 at University of Poonch, Rawalakot, Azad Jammu and Kashmir. Treatments included un-amended control, KS41 (PGPR strain 1), KS42 (PGPR strain 2), UN (urea N), KS41 + UN and KS42 + UN. Nitrogen was applied at a rate of 150 kg N ha-1. The experiment was laid out in two factorial split-plot arrangement under randomized complete block design (RCBD) with three replications. Among treatments, PGPRs with UN illustrated maximum plant height, stem diameter, shoot and root dry matter of sunflower. Similarly, chlorophyll contents, head diameter, and number of days taken to flower initiation, completion and maturity were significantly affected by the combined application of UN with KS41 and KS42 compared to their sole application. When compared with control overall increase in morphological and phenological traits ranged between 27 to 65 %. Among cultivars, SFH-70 morphological and phenological traits responded more positively towards combined application of PGPR and UN and were significantly higher than RA-533. Results from this study indicated that combined application of PGPR and UN significantly enhanced most of the morphological and phenological traits of sunflower cultivars. However, further investigations are required to confirm the effect of PGPR application with different N sources, N rates and soil conditions